Civil economy another idea of the market - Bruni, Luigino 1966-; Zamagni, Stefano 1943- (Agenda, 2023)
This title provides a succinct introduction to the civil economy approach and its history, which draws on the rich Italian tradition of civic humanism and which places well-being, virtue and the common good alongside more familiar economic goals
Translated from the Italian. - Previously issued in print: 2016. - Includes bibliographical references and index
Keywords: Geschichte; Economics; Sozialstaat; Humanismus; Klassische Nationalökonomie; Wohlfahrtsstaat; Christliche Sozialethik; Wirtschaftsphilosophie; Zivilgesellschaft; Katholische Soziallehre; Ideengeschichte; Wirtschaftsethik; Wirtschaftstheorie; Großbritannien; Italien